2017
DOI: 10.1111/are.13463
|View full text |Cite
|
Sign up to set email alerts
|

Habituation and conditioning in gilthead sea bream (Sparus aurata ): Effects of aversive stimuli, reward and social hierarchies

Abstract: To tailor the farming environment to a fish species, we should understand the species-specific responses to stimuli, including the degree of adaption and learning.Groups of gilthead sea bream were given a delay Pavlovian conditioning regime using a conditioning stimulus (CS) of light flashes signalling arrival of food. Controls were exposed to light flashes unrelated to feeding. Fish in both treatments showed an initial fear response of moving away from the CS combined with reduced swimming speed. In subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
7
2
Order By: Relevance
“…In the control group, the conditioned response tended to be higher than baseline level after 8 trials and it was higher in the control than in the stressed group at trial 5, showing the remarkable learning skills of the rainbow trout in a classical appetitive conditioning paradigm. The acquisition is faster than previously observed in sea bream ( Sparus aurata ), which associate a US with a CS after approximately 16 trials (Folkedal et al, 2018). The inherent stress effect of a reduced appetite, as demonstrated by a significant reduction in growth in the stressed group compared to the control group, might represent an explanation of the impaired learning in the stressed group.…”
Section: Discussioncontrasting
confidence: 53%
“…In the control group, the conditioned response tended to be higher than baseline level after 8 trials and it was higher in the control than in the stressed group at trial 5, showing the remarkable learning skills of the rainbow trout in a classical appetitive conditioning paradigm. The acquisition is faster than previously observed in sea bream ( Sparus aurata ), which associate a US with a CS after approximately 16 trials (Folkedal et al, 2018). The inherent stress effect of a reduced appetite, as demonstrated by a significant reduction in growth in the stressed group compared to the control group, might represent an explanation of the impaired learning in the stressed group.…”
Section: Discussioncontrasting
confidence: 53%
“…2010; Folkedal et al . 2018). Reward conditioning has been used to successfully reduce the stress response of Atlantic cod ( Gadus morhua ) to the moving of a dip net in the water (Nilsson et al .…”
Section: Resultsmentioning
confidence: 99%
“…Schreck et al (1995) observed an increased resistance to pathogens, reduced mortality during transport and decreased physiological response to other stressors in juvenile Chinook salmon (Oncorhynchus tshawytscha) that underwent a positive conditioning regime to associate dewatering for transport with feeding. Both Atlantic salmon and gilthead sea bream (Sparus aurata) went from being frightened by an initially aversive stimulus (flashing lights) to exhibiting anticipatory behaviour towards the same stimulus after undergoing positive conditioning and habituation (Bratland et al 2010;Folkedal et al 2018). Reward conditioning has been used to successfully reduce the stress response of Atlantic cod (Gadus morhua) to the moving of a dip net in the water (Nilsson et al 2012).…”
Section: Harnessing Innate Behaviours In Aquaculturementioning
confidence: 99%
“…This fact makes sense since, in most aquatic environments, the complexity of surroundings is associated with the need to locate shelters, feeding areas, predators, etc., thus exemplifying the adaptive value of learning ability in these environments. In this scenario, the occurrence of classical conditioning was recently demonstrated in several studies of fish species, such as zebrafish (Danio rerio) (Manabe et al 2013;Doyle et al 2017), St. Peter's fish (Sarotherodon galilgeus) (Zion et al 2011a, b), Atlantic salmon (Salmo salar) (Bratland et al 2010), and Dourada (Sparus aurata) (Folkedal et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…In these studies, the conditioned stimulus is usually some sort of light and/or sound, which is tested in groups of fish aiming to facilitate the management of these animals (Moreira and Volpato 2004;Bratland et al 2010;Zion and Barki 2012;Folkedal et al 2018). However, when performing experiments to evaluate individual responses (e.g., understanding learning mechanisms), the effectiveness of this conditioning method may be compromised when fish located in nearby aquariums Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10211-018-0297-4) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%